An operation synchronization model for distribution center in E-commerce logistics service. (January 2020) - Yu, Ying; Yu, Chenglin; Xu, Gangyan; Zhong, Ray Y.; Huang, George Q.
Highlights: Firstly, synchronization performance in distribution centers is specifically related to E-commerce scenarios. Secondly, it introduces an approach to measurement that is able to address the distribution center operation synchronization (DCOS) problem. Thirdly, we examine both synchronization and punctuality so as to figure out the trade-off relationship between them. Some of our observations are particularly significant. Fourthly, here is the fact that if a synchronization penalty is applied, better operation scheduling in the distribution center can be achieved. This in turn can have the benefit of increasing the efficient utilization of all resources. Abstract: This paper is among the first that proposes a synchronization measurement model for the distribution centre operation synchronization (DCOS) problem, which aims to ensure the E-commerce order's punctuality and synchronization at the same time. The main motivation of DCOS is that the intensified competition in E-commerce market makes efficient E-commerce logistics service extremely important, which means saving logistics cost and ensuring customer service at the same time. The synchronized operation may be a possible solution to ensure efficient order transhipment in the distribution center and to save cost. We thus introduce a measurement approach that is able to address the distribution center operation synchronization (DCOS) problem such as the trade-off relationship between synchronization and punctuality. In order to get persuasive conclusions, we adopt data from a real practice case and apply CPLEX to get the optimal solution. Our computational results show that considering the asynchronous cost in the total cost objective function will greatly improve the operation synchronization in the distribution center, by saving the storage space, the equipment, and the labour resources. And if the storage cost is in a reasonable range, the synchronized operation can be realized while the punctuality is also optimized. It is found in our case that the most efficient way to improve distribution center operation is expanding inbound operation capacity.